2023
DOI: 10.3390/pharmaceutics15030774
|View full text |Cite
|
Sign up to set email alerts
|

Approved Nanomedicine against Diseases

Abstract: Nanomedicine is a branch of medicine using nanotechnology to prevent and treat diseases. Nanotechnology represents one of the most effective approaches in elevating a drug‘s treatment efficacy and reducing toxicity by improving drug solubility, altering biodistribution, and controlling the release. The development of nanotechnology and materials has brought a profound revolution to medicine, significantly affecting the treatment of various major diseases such as cancer, injection, and cardiovascular diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 229 publications
0
21
0
Order By: Relevance
“…To overcome these hurdles, liposomes offer many advantages as antibiotic nanocarriers. These lipid-based nanosystems may reduce dose and frequency of administrations, prevent enzymatic degradation, avoid drug efflux mechanisms, and overcome outer membranes [ 18 , 31 , 73 , 74 ]. In the case of RFB, previous studies in a murine model of disseminated Mycobacterium tuberculosis infection demonstrated a significantly superior antimycobacterial effect of RFB-loaded liposomes in the spleen and liver, compared to free antibiotic [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these hurdles, liposomes offer many advantages as antibiotic nanocarriers. These lipid-based nanosystems may reduce dose and frequency of administrations, prevent enzymatic degradation, avoid drug efflux mechanisms, and overcome outer membranes [ 18 , 31 , 73 , 74 ]. In the case of RFB, previous studies in a murine model of disseminated Mycobacterium tuberculosis infection demonstrated a significantly superior antimycobacterial effect of RFB-loaded liposomes in the spleen and liver, compared to free antibiotic [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, there are more than 100 nanomedicines approved on the market, mainly for cancer therapy (53%) and infection (14%) 72,73 . However, there are several challenges limited the development of nanomedicine, and the applications of nanoparticles in metabolic diseases are still far from fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of drugs and nanomaterials will provide hope for patient survival ( Van der Meel et al, 2019 ; Jia et al, 2023 ). Multi-drug combination is one of the important means to improve anti-cancer efficacy, and it is also a general trend in the field of drug research and development ( Detappe et al, 2023 ).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%